Rewild yourself : 23 spellbinding ways to make nature more visible - Barnes, Simon, 1969-; Wright,L. Cindy, ....- (London : Simon & Schuster, 2020)
Now you don't see it. Now you do. Twenty-three ways to make hidden wildlife appear before your eyes. We're not just losing the wild world. We're no longer noticing it. We've lost the habit of looking and seeing and listening and hearing. Now, in Rewild Yourself, Simon Barnes provides 23 wonderful tips to bring wild creatures into the middle of your own world. With a few new techniques, a little new equipment and, above all, a new way of thinking, birds hidden in the treetops will shed their cloak of anonymity and creatures of the darkness will enter the light of your consciousness.
Keywords: Natuur